2018
DOI: 10.1021/acs.analchem.7b04828
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Live-Cell Interferometry: A New Method for Quantifying Tumor Drug Resistance and Heterogeneity

Abstract: We report the development of high-speed live-cell interferometry (HSLCI), a new multisample, multidrug testing platform for directly measuring tumor therapy response via real-time optical cell biomass measurements. As a proof of concept, we show that HSLCI rapidly profiles changes in biomass in BRAF inhibitor (BRAFi)-sensitive parental melanoma cell lines and in their isogenic BRAFi-resistant sublines. We show reproducible results from two different HSLCI platforms at two institutions that generate biomass kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 49 publications
1
61
0
Order By: Relevance
“…Earlier work by our group has established that live cell mass accumulation rates measured by QPI can be used to assess response to cytostatic or cytotoxic cancer drugs. These mass accumulation-based responses were found to be concordant with traditional cell counting and fluorescent reporter viability assays in a variety of cancer types, including breast, multiple myeloma, and melanoma [9][10][11].…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Earlier work by our group has established that live cell mass accumulation rates measured by QPI can be used to assess response to cytostatic or cytotoxic cancer drugs. These mass accumulation-based responses were found to be concordant with traditional cell counting and fluorescent reporter viability assays in a variety of cancer types, including breast, multiple myeloma, and melanoma [9][10][11].…”
Section: Introductionsupporting
confidence: 52%
“…Though statistically significant, the small magnitude of response and the lack of a clear relationship to escalating doses suggests that pablociclib would not be an effective treatment in vivo for this tumor. Past experience with HSLCI dose response curves informs us that a fluctuation of this magnitude (∼0.1%) is relatively insignificant and within typical random error (such as tumor sampling heterogeneity or pipetting error) for such samples [9,10]. This conclusion is supported by the results of a luciferase assay, which showed a similar marginal response at the highest tested dose of 10 µM.…”
Section: Cdk 4/6 Inhibitorsmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, results presented on the individual cellular level of prostate cancer cells and mouse fibroblast cells treated with cell death-inducing drugs showed that these cell types behaved very differently [82]. Using rapid profiling with high-speed live-cell interferometry, Huang and co-workers recently showed that the proto-oncogene B-Raf (BRAF)-inhibitor sensitive melanoma cell lines differed in measurements of optical cell biomass [62]. Interestingly, within 24 h, biomass kinetic signatures were obtained for three Interestingly, several DH parameters that were measured, including cell number, area, thickness, and volume, were decreased after Etoposide treatment of the Jurkat cells (Table 2).…”
Section: Cell Death Studies With Qpimentioning
confidence: 99%
“…The nucleus , actin cytoskeleton , membrane‐bound organelles , and cytoplasm contribute to the cell phase profile. Events that significantly affect a cell's morphology or subcellular phase texture are often detected longitudinally or by comparing distinct cell populations . For example, time‐lapse imaging of single cells reveals the effects on phase signals of agents inducing apoptosis , cytoskeletal disruption , or reduced proliferation .…”
mentioning
confidence: 99%